PENGARUH LATIHAN LARI BOLAK BALIK TERHADAP KELINCAHAN ATLET FUTSAL PUTRA TIM ACCASIA PEKANBARU - Fernando, Ravelito; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is that during futsal matches, less players do the movement without the ball so that the opportunity to get acceptance passing ball from friends is often cut by opponents. This type of research is a type of experimental research to see the effect of the form of exerxise. The purpose of research is to look at the effect back and forth training on the agility of the men?s futsal athletes Accasia team Pekanbaru. The population in this research is the Accasia team Pekanbaru, which numbered 18 people. The sampling technique is to use a purposive sampling technique, where taking a portion of the population is sampled. Data collection techniques obtained from pre-test and post-test. The instrument in this study uses the agility T test as a measure of agility. After that, the data is then statistically processed to test the normality using the lilifours test at a significant level of 0.05 a. Based on the analysis of the normality of the data X, it gives a LoMax of 0.140 and an Ltable of 0.258, which means LoMax <Ltable. while the variable Y yields LoMax of 0.141 and Ltable of 0.258. This means LoMax <Ltable, the analysis was performed by t-test. Based on the analysis and discussion, it can be concluded that there is an effect of running training back and forth on the agility of the men?s futsal athletes team of the Accasia team Pekanbaru proven by Tcount of 9.69 and Ttable 1.812. Means Tcound > Ttable at the level ? = 0.05. Key Words: Running Back and Forth, Agility